2015
DOI: 10.1089/zeb.2014.1031
|View full text |Cite
|
Sign up to set email alerts
|

Nonhatching DecapsulatedArtemiaCysts As a Replacement toArtemiaNauplii in Juvenile and Adult Zebrafish Culture

Abstract: Feeding Artemia nauplii as the main nutrition source for zebrafish is a common practice for many research facilities. Culturing live feed can be time-consuming and requires additional equipment to be purchased, maintained, and cleaned. Nonhatching decapsulated Artemia cysts (decaps) are a commercially available product that can be fed directly to fish. Several other ornamental fish species have been successfully cultured using decaps. Replacing Artemia nauplii with decaps could reduce the overall time and cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…Adult zebrafish were maintained at the University of Minnesota Zebrafish Core Facility using standard practices (Tye et al, 2015). Embryos and larvae were raised at 28.5°C with a 14-h light:10-h dark cycle in embryo water containing 60 µg/mL Instant Ocean (Blacksburg, VA) Sea Salt.…”
Section: Methodsmentioning
confidence: 99%
“…Adult zebrafish were maintained at the University of Minnesota Zebrafish Core Facility using standard practices (Tye et al, 2015). Embryos and larvae were raised at 28.5°C with a 14-h light:10-h dark cycle in embryo water containing 60 µg/mL Instant Ocean (Blacksburg, VA) Sea Salt.…”
Section: Methodsmentioning
confidence: 99%
“…The four studies that were not included having been initially deemed suitable were excluded because they produced significant publication bias ( n = 1) or were the wrong age for the parameters for which they presented data ( n = 3) 8,17–19 . Four studies were identified which assessed reproduction; however, this was below our threshold for inclusion for statistical comparison and therefore were not included any further in the analysis 2023 .…”
Section: Resultsmentioning
confidence: 99%
“…En pez cebra se ha demostrado la necesidad de tenerlos en grupos sociales adecuados, tanto en número como en tamaño (más de 10 peces), y descartar el uso de plantas, que serán sólo usadas cuando estén en aislamiento (9). También el uso de alimento vivo como la Artemia es una forma eficaz de mejorar los índices reproductivos, por el alto contenido en ácidos grasos poliinsaturados y estimular su instinto depredador 10 . La dieta natural del pez cebra, originario de Asia 11 , está compuesta básicamente por invertebrados, especialmente en la época monzónica, que es la que prefieren para su reproducción 12 .…”
Section: Gestión Del Bienestar: In Situ Y a Prioriunclassified